A Three-Year Mandatory Student Research Program in an Undergraduate Medical Curriculum in Turkey - (:unkn) unknown (KUWAIT MEDICAL ASSOC, 2010)
Objective: To evaluate the seven-year experience of the mandatory undergraduate student research program of Marmara University School of Medicine, Turkey Design: Retrospective Setting: Marmara University School of Medicine, Turkey Subjects: Undergraduate students (from Year I, II and III; n = 289), mentors (n = 54) and graduates (n = 30) were enrolled They were all involved in a longitudinal, mandatory and interdisciplinary research program. Students conducted a project under the supervision of a mentor in small groups and every year they improved their research skills step-by-step around specific themes Each year the program ended with the Marmara Student Congress (MaSCo), at which all projects were presented Interventions: Student feedback evaluation, pre-prepared questionnaire filled by mentors and telephonic interview of randomly selected graduates Main Outcome Measures: Number of projects presented in medical congresses, published in medical journals and feedback from students, mentors and graduates Results: Between the years 2002 - 2007, students presented 467 research projects in MaSCo. Out of a total of 205, 2(nd) and 3(rd) year projects, 10 were published in international journals (4 87%) and nine (4 39%) in Turkish journals, 51(24.8%) were presented in national and 22 (10.1%) were presented in international congresses. Chi square trend analysis showed that students' satisfaction in all Items of research activity Increased from first to the third year. Sixty-three percent of graduates found undergraduate research activity beneficial. Conclusions: Research programs should be one of the components of undergraduate medical education. We recommend that such programs be mandatory to develop research skills step-by-step
Keywords: mentors; research activities; teaching methods; ATTITUDES; SCHOOL